PENERAPAN PERMAINAN KARTU KUARTET UNTUK MENINGKATKAN MINAT BELAJAR PENGAMALAN SILA PANCASILA KELAS II SDN MAGERSARI SIDOARJO - Yasin, Fajar Nur; Susanti, Elenanik (Jurnal Muassis Pendidikan Dasar, 2023)
This research aims to improve student learning outcomes through the use of Quartet Card media in Pancasila Education Subjects, Pancasila Practice Material for Class II SD Magersari. This type of research is classroom action research (PTK). The subjects of this research were 36 class II students at Magersari Elementary School, consisting of 22 male students and 14 female students. This research was carried out in two action cycles. The implementation stages of cycle 1 were carried out in two meetings and cycle 2 was carried out in two meetings. Data collection was carried out using learning results tests and observation sheets. The data that has been collected is then analyzed qualitatively. The results of the research show that the use of quartet card media can increase interest in learning about Pancasila Education for class II students at SDN Magersari seen from the results of tests carried out in two cycles which show very good results with classical learning completion in cycle I reaching a percentage of 55.5% out of a total of 36 students in one class and cycle II reached a percentage of 83.3% of the total of 36 students. In order to achieve very good qualifications, it can be concluded that using the quartet card learning media can increase the learning interest of class II students at Magersari Elementary School.